Language as a Weapon: The Logical Fallacies in Political Discourse - Muhammad Ifan (Winaya Inspirasi Nusantara Foundation, 2022)
In modern political discourse, language serves as both a means of communication and a strategic instrument for influencing public reasoning and consolidating ideological dominance. This study examines how political figures utilise language to disseminate logical fallacies that skew rational judgement and influence public perception. The main aim is to discover, classify, and critically assess the linguistic strategies that incorporate faulty reasoning in political discourse. The study utilises a critical review methodology to synthesise findings from 45 peer-reviewed journal publications published between 2010 and 2024 in the disciplines of linguistics, political science, philosophy, and discourse analysis. Data were gathered via systematic searches in Scopus-indexed databases and analysed thematically through qualitative content analysis and the principles of critical discourse analysis. The results indicate four prevailing patterns: (1) the tactical employment of informal fallacies, including ad hominem and false dilemma; (2) the rhetorical amplification of fallacies via causal and contrastive connectives; (3) the emotional framing of arguments to evade critical examination; and (4) the normalisation of erroneous reasoning through media and political discourse repetition. These findings highlight the necessity for improved critical literacy and public consciousness regarding rhetorical manipulation in democratic nations. The research enhances multidisciplinary discourse on language and authority and provides practical applications for education, journalism, and civic participation.